Antiprotonic Atoms as Gateways to HCI - Lappo, Lidia; Zieliński, Jakub; Gustafsson, Fredrik P.; Grosbart, Malgorzata; Kornakov, Georgy; Doser, Michael (Atoms, 2025)
The present study investigates the production of highly charged ions (HCIs) through the novel application of antiprotonic atoms and explores their potential for studying atomic and nuclear structures. Utilizing the Geant4 simulation toolkit, comprehensive simulations were conducted for all known isotopes with atomic numbers below 100. These simulations recorded key parameters of the resulting nuclear fragments, including mass, momentum, charge, and yield. The results obtained from this study offer valuable insights into the mechanisms of HCI production and provide a foundation for planning and analyzing future experimental investigations. This work demonstrates the feasibility of using antiprotonic atoms to advance nuclear and atomic physics research.